Out of DSM: Depathologizing Homosexuality - Jack Drescher (Behavioral Sciences, 2015)
In 1973, the American Psychiatric Association (APA) removed the diagnosis of “homosexuality” from the second edition of its Diagnostic and Statistical Manual (DSM). This resulted after comparing competing theories, those that pathologized homosexuality and those that viewed it as normal. In an effort to explain how that decision came about, this paper reviews some historical scientific theories and arguments that first led to the placement of homosexuality in DSM-I and DSM-II as well as alternative theories that eventually led to its removal from DSM III and subsequent editions of the manual. The paper concludes with a discussion of the sociocultural aftermath of that 1973 decision.